SISTEM MANAJEMEN DISTRIBUSI SUPLAI USAHA KECIL MENENGAH BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Yuliana, Ade; Pratama, Mukhammad Ilham Ramdan; Sudrajat, Ari (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
Conventional inventory management poses a major challenge for Usaha Kecil Menengah (UKM), as it frequently leads to various operational obstacles including inaccurate stock data, difficulties in financial reporting, and insufficient transaction transparency for business owners. This study aims to design and implement a web-based system capable of managing supply distribution at UKM Bukit Berlian as a replacement for the existing ledger-based recording method. System development follows the Software Development Life Cycle (SDLC) methodology using the waterfall model. The system was developed using Laravel framework version 8.75 with MySQL as the database management system. System functionality was verified through Black Box Testing, confirming that all features operated in accordance with the defined specifications. User acceptance evaluation was subsequently conducted through User Acceptance Testing (UAT) involving 10 respondents, yielding an acceptance rate of 84.2%, which is classified as very good. The findings indicate that the implementation of this system successfully improved inventory administration efficiency, supported more data-driven decision-making processes, and enhanced reporting transparency for UMKM partners.